2020
DOI: 10.1186/s12979-020-00189-7
|View full text |Cite|
|
Sign up to set email alerts
|

Classical and lectin complement pathways and markers of inflammation for investigation of susceptibility to infections among healthy older adults

Abstract: Background: There is increasing recognition of the significance of chronic, low-level inflammation in older adults, or "inflammaging." Innate immune responses and host-bacterial interactions are recognized as key factors in inflammaging. Inflammatory cytokine IL-6, and complement protein C1q have been identified as biomarkers for the development of frailty and aging-related diseases. Older adults are also susceptible to infections with serotypes of Streptococcus pneumoniae that bind ficolin-2, a component of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Our COVID-19 patient population had a median age of 72 years (range 28-88 years), which was significantly older than dialysis control (62 years, p=0.01) and healthy control (49 years, p<0.0001) cohorts ( Table 1 ). We did not consider this to be a limitation because lectin protein levels do not differ significantly between older and younger adults ( 17 ). The mean estimated glomerular filtration rates (eGFR) at presentation of the patients not established on maintenance dialysis were 11ml/min/1.73m2 in the CKD patients and 23 ml/min/1.73m2 (range 12-36ml/min/1.73m2) in the kidney transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our COVID-19 patient population had a median age of 72 years (range 28-88 years), which was significantly older than dialysis control (62 years, p=0.01) and healthy control (49 years, p<0.0001) cohorts ( Table 1 ). We did not consider this to be a limitation because lectin protein levels do not differ significantly between older and younger adults ( 17 ). The mean estimated glomerular filtration rates (eGFR) at presentation of the patients not established on maintenance dialysis were 11ml/min/1.73m2 in the CKD patients and 23 ml/min/1.73m2 (range 12-36ml/min/1.73m2) in the kidney transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Increased H-ficolin and decreased MBL and MASP-3 levels have been demonstrated in serial plasma samples from patients with sepsis ( 15 , 16 ). In contrast, no significant differences have been detected in lectin pathway protein levels between young and old healthy adults ( 17 ). The potential for lectin pathway PRMs to interact with coronavirus is demonstrated by in vitro binding of MBL to SARS-CoV proteins ( 18 ).…”
Section: Introductionmentioning
confidence: 93%
“…The complement lectin pathway is activated when a pattern recognition receptor, such as mannose binding lectin (MBL), binds to pathogen-associated molecular patterns expressed on the surface of invading microorganisms ( 29 ). The complement cascade is then initiated by MBL forming complexes with MBL-associated serine proteases 1 and 2 (MASP-1 and MASP-2, respectively) in a similar fashion that C1 is activated through the classical pathway, leading to C4 and C2 cleavage and assembly of the C3 convertase ( 30 ). A historic case-control study on 569 SARS patients demonstrated a role of MBL gene polymorphisms in contributing to the susceptibility of viral invasion, and implied that the complement lectin pathway represents the “first line of defense” against SARS-CoV infection ( 31 , 32 ).…”
Section: Pharmacological Complement Inhibitionmentioning
confidence: 99%
“…The classical pathway recognises immune complexes, comprising of either IgG or IgM coupled with a pathogen or non-self-antigen, triggering a conformational change in complement component (C)1q, which sequentially leads to activation of C1r along with C1s and cleaving of C2 and C4 [98] . The same outcome is shared by the lectin pathway, which relies upon a multi-protein complex containing mannan-binding lectin and two protease zymogens (MASP-1 and MASP-2) to be activated, and recognises carbohydrate ligands upon cell surfaces [99] , [100] . The third and final route of activation, known as the alternative pathway, does not lead to the creation of the C4bC2a configuration C3 convertase.…”
Section: Immunological Responses In Covid-19mentioning
confidence: 99%